Prognostic value of a predictive score based on functional parameters for clinical outcome in patients with decompensated cirrhosis of the liver - Jasminka Mujkanović; Kenana Ljuca; Amir Tursunović; Nadina Ljuca; Dževad Džananović; Farid Ljuca (Medicinski glasnik, 2023)
Aim: To create a predictive score based on functional parameters of the liver and determine its prognostic value in survival of patients with decompensated cirrhosis. Methods: Retrospective observational study included 91 consecutive patients with decompensated cirrhosis. Functional parameters (bilirubin, AST - aspartate aminotransferase, ALT - alanine aminotransferase, ALP - alkaline phosphatase, GGT - gammaglutamyltranferase, albumin, prothrombin time, platelet count, haematocrit and creatinine), Child-Pugh (CP) and Model of EndStage Liver Disease (MELD) scores have been measured at first hospitalization and at every exacerbation episode over follow-up period of 24 months. Results: Using Cox regression analysis, we found that age (OR=1.206; p=0.03; 95% CI=1.019-1.428), serum bilirubin (OR=1.017; p=0.003; 95% CI=1.006-1.029), INR (International normalized ratio) (OR=6.262; p=0.002; 95% CI=1.924-20.378) and serum creatinine (OR=1.019; p=0.005; 95% CI=1.006- 1.032) had statistically strong association with the incidence of a six-month mortality. Age (OR=1.120; p=0.006; 95% CI=1.033- 1.214), serum bilirubin (OR=1.021; p=0.0001; 95% CI=1.010-1.032), GGT (OR=1.007; p=0.023; 95% CI=1.001-1.014), INR (OR=9.571; p=0.001; 95% CI=2.610-35.098), haematocrit (OR=0.695; p=0.001; 95% CI=0.559-0.864) and serum creatinine (OR=1.023; p=0.0001; 95% CI=1.011-1.035) showed an increased the risk for a 24-month lethal outcome. Predictive score derived from liver functional parameters, CP and MELD scores, each independently has shown a high degree of death prediction after 6 or 24 months in patients with end-stage liver disease. Conclusion: Predictive score derived from liver functional parameters had a better prognostic value for short-term and long-term mortality comparing to MELD and Child-Pugh score.
Keywords: end-stage liver disease; survival rate; transplantation; waiting list